"Carol Project" : plan of townsite layout and services in Areas 1 and 2, Wabush Lake, Labrador, NFLD - Iron Ore Company of Canada. (Ottawa (Ont.), 1959)
Hand coloured. Blueline print. North arrow. Oriented with north to the upper left. Relief shown by contours and spot heights. Shows total number of housing units and yearly progress of construction. Includes detailed legend.